Bioproduction dynamics ofPenaeus indicus H. Milne Edwards in modular system - Manikandavelu, D (Indian Journal of Fisheries, 2011)
Specific growth rate of white prawn Penaeus indicus was monitored in a miniature modular system. As the size of the module increased, reduction in ammonia generation could be seen. Similar trend was also noticed with respect to organic load. Reduction in daily differential in oxygen as the module size increased, resulted in favourable specific growth rate in larger modules. The cumulative impact of ammonia, organic load (COD) and hydrogen sulphide was well indicated in specific growth rate. Surface area also appeared to play positive role on specific growth rate. Thus this modular system can serve as a new means to shrimp farming, striking a balance between ecological conservation and economic considerations